Homophobia in the Classroom: One Teacher’s Response - Peters, Cynthia (Radical Teacher, 2019)
A teacher rescues students from mutually reinforcing their homophobia by talking about her own sister, a lesbian, and then asking them to share family photo albums in the following class.